How Did School Meal Access Change during the COVID-19 Pandemic? A Two-Step Floating Catchment Area Analysis of a Large Metropolitan Area - Jason Jabbari (MDPI AG, 2021)
SARS-CoV-2 (COVID-19) resulted in school closures and contingencies across the U.S. that limited access to school meals for students. While some schools attempted to provide alternative meal access points where students or parents could pick up meals, many students—especially those in low-income households—lacked adequate transportation to these access points. Thus, physical proximity to meal access points was particularly important during the pandemic. In this study, we explore how school meal access changed during the COVID-19 pandemic, especially as it relates to race/ethnicity and socio-economic status. Taking into account both the “supply” (meal access points) and the “demand” (low-income students) for free meals, we employed a two-step floating catchment area analysis to compare meal accessibility in St. Louis, Missouri before and during the pandemic in the spring and summer of 2019 and 2020. Overall, while school meal access decreased during the spring of 2020 during the early months of the pandemic, it increased during the summer of 2020. Moreover, increased access was greatest in low-income areas and areas with a higher proportion of Black residents. Thus, continuing new policies that expanded access to school meals—especially for summer meal programs—could lead to positive long-term impacts on children’s health and well-being.